2017
DOI: 10.1016/j.neuropharm.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bingeing on fat during adolescence on the reinforcing effects of cocaine in adult male mice

Abstract: Binge eating is a specific form of overeating characterized by intermittent excessive eating. In addition to altering the neurobiological reward system, several studies have highlighted that consumption of palatable food increases vulnerability to drug use. The aim of the present study was to evaluate the effects of a high-fat diet consumed in a binge pattern during adolescence on the reinforcing effects of cocaine. After 40 days of binge-eating for 2 h, three days a week (PND 29-69), the reinforcing effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 109 publications
7
38
1
Order By: Relevance
“…63 Moreover, two studies found that mice or rats intermittently and time-limited fed with a palatable diet over several weeks displayed a reduction of plasma ghrelin levels immediately after the last binge eating event. 64,65 Other studies, however, could not confirm these observations and found that rats time-limited fed with palatable diets, either daily or intermittently, over several weeks did not change plasma ghrelin levels in anticipation to the scheduled meals compared to control rats. 50,66 Also, another study found that female rats with daily and limited access to a palatable diet over several weeks displayed lower plasma ghrelin levels under fasting compared to control rats.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…63 Moreover, two studies found that mice or rats intermittently and time-limited fed with a palatable diet over several weeks displayed a reduction of plasma ghrelin levels immediately after the last binge eating event. 64,65 Other studies, however, could not confirm these observations and found that rats time-limited fed with palatable diets, either daily or intermittently, over several weeks did not change plasma ghrelin levels in anticipation to the scheduled meals compared to control rats. 50,66 Also, another study found that female rats with daily and limited access to a palatable diet over several weeks displayed lower plasma ghrelin levels under fasting compared to control rats.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, one study found that increments of plasma ghrelin levels positively correlated with food anticipatory activity and that a GHSR antagonist decreased such behaviour, whereas another study showed that blockade of plasma ghrelin increments attenuated the magnitude of binge‐like HF intake . Moreover, two studies found that mice or rats intermittently and time‐limited fed with a palatable diet over several weeks displayed a reduction of plasma ghrelin levels immediately after the last binge eating event . Other studies, however, could not confirm these observations and found that rats time‐limited fed with palatable diets, either daily or intermittently, over several weeks did not change plasma ghrelin levels in anticipation to the scheduled meals compared to control rats .…”
Section: Discussionmentioning
confidence: 97%
“…Drug use during this critical period of development often predisposes to an increased likelihood of continued use into adulthood (Arteaga, Chen, & Reynolds, ). Moreover, social (e.g., peer influence), economic (e.g., low social status), hormonal (increase in adrenal and gonadal hormones), neurochemical (changes in DA neurotransmission) and dietary (high‐fat/sugar diets) conditions during adolescence also contribute to increased vulnerability to drug use (Blanco‐Gandía, Cantacorps et al., , Blanco‐Gandía, Ledesma et al., ; Spear, ). Social stress in early life, such as bullying at school or child abuse, can have several consequences in adulthood (de Groot, van Milligen, Moonen‐Leusen, Thomas, & Koolhaas, ; Lumley, Sipos, Charles, Charles, & Meyerhoff, ).…”
Section: Social Defeat Stress During Adolescencementioning
confidence: 99%
“…Nevertheless, it has been proposed that binge-eating, as a maladaptive behavior, could work as a gateway for the development of drug addiction [ 30 33 ]. We have recently confirmed that bingeing on fat increases cocaine and EtOH consumption and the conditioned rewarding effects of both drugs [ 32 , 33 ]. First, we demonstrated that animals bingeing on fat were more sensitive to the reinforcing effects of a subthreshold dose of cocaine in the conditioned place preference and presented enhanced cocaine self-administration.…”
Section: Introductionmentioning
confidence: 81%